HAND HYGIENE AND HEALTHCARE-RELATED INFECTIONS: A LITERATURE REVIEW - Sacramento Costa, Verena (Health and Society, 2023)
The aim of this study was to identify the main risks of healthcare-associated infections and the role of hand hygiene. From this objective, the research problem that guided all the work was raised, where it was asked: what is the role of hand hygiene in health care? The hypothesis for this question includes that if health professionals properly wash their hands, they prevent the emergence of infections and cross-contamination. The approach on the subject becomes important, in view of the increased demand for health care due to various problems such as the pandemic itself. On the other hand, it is extremely important to pay attention to adequate and correct protocols so that the possibilities of the appearance of infections and various contaminations that could be avoided only with correct hand hygiene are increasingly reduced. The methodology used for the construction of this text was bibliographical research. The nature of the research was basic, as the intention was to produce knowledge through the investigation of the research problem. Materials published between 1997 and 2021 and written in both Portuguese and English were used. The articles were read, the due summaries were made and later the data relevant to the research was removed. The results pointed to the extreme importance of the professionals’ behavior regarding proper hygiene and standardized techniques.